Diet-induced obesity causes metabolic, endocrine and cardiac alterations in spontaneously hypertensive rats - Oliveira Junior, Silvio A. [UNESP] (2010)
Background: Although obesity has been associated with several effects in rodents, few investigations have evaluated the metabolic, endocrine, and cardiac parameters of spontaneously hypertensive rats (SHR) with dietary-induced obesity. The current study analyzed the influence of dietary-induced obesity on metabolic, endocrine, and cardiac characteristics in SHR.Material/Methods: Male SHR were distributed in 2 groups: C-SHR (n=10) and OB-SHR (n=10). While C-SHR received a standard commercial diet (CD; 3.2 kcal/g), OB-SHR were submitted to a hypercaloric diet (HD; 4.6 kcal/g) for 20 weeks. Nutritional, metabolic, and endocrine evaluation involved measurement of calorie intake, dietary efficiency, body weight, adiposity, glycemia, triacylglycerol, insulin, and leptin. Cardiovascular evaluation integrated systolic blood pressure (SBP), echocardiography, gross and ultrastructural morphology, and myosin heavy chain (MHC) analyses of the myocardium.Results: Animals in OB-SHR had greater values of BW, adiposity, triacylglycerol, and leptin and impaired glycemic tolerance compared with the C-SHR group. In the cardiovascular context, dietary-induced obesity increased interstitial collagen, the cardiomyocyte area, and the relative expression of beta-MHC, and well as beta-/alpha-isoform ratio of MHC. Likewise, OB-SHR showed ultrastructural morphologic alterations, with loss and disorganization of myofilaments, lipid droplets, severe mitochondrial damage, and T-tubule dilation. Concerning the in-vivo cardiovascular profile, although SBP and systolic function were unchanged by dietary-induced obesity, echocardiography results evidenced impaired diastolic function in OB-SHR in relation to their control counterparts.Conclusions: Diet-induced obesity was associated with endocrine alterations, and it accentuated cardiac remodeling, promoting diastolic dysfunction of restrictive filling pattern in the SHR strain.